The Effect of Discovery Learning to Students’ Mathematics Performance - Robert B. Golingan; June Rey S. Sulatra (International Journal on Integrated Education, 2022)
This quasi-experimental research was conducted to determine the effect of discovery learning to the academic performance of students. The participants of the study were randomly selected seventy (70) Grade 10 students in Mathematics class. Two (2) sections with 35 students each were the control and experimental groups. The findings showed that students did not meet the expectation in terms of the level of their performance in Mathematics before the intervention. After the intervention, the level of performance of the experimental group advanced to very satisfactory and the non-experimental group advanced to satisfactory. Significant differences were noted between the pre-test and post-test scores of each group. This shows that both of the interventions have a positive effect on students’ performance in Mathematics. Comparing the post-test scores between the control and experimental groups, significant difference was recorded indicating the discovery learning group has higher mathematics performance compared to non-discovery learning group.